FAMILY PERCEPTION AND PARTICIPATION AND ITS INFLUENCE ON THEIR WEALTH - Lutfi Sri Legowo Utami; Istiqlaliyah Muflikati; Megawati Simanjuntak (Economic Journal of Emerging Markets)
Micro Financial Institution (MFI) is an alternative financial institution that helps micro entrepreneurs and poor families to get flexible loans. This study analyzes family perception and participation on micro financial institution and their influence on family welfare. It analyzes the cases of Bina Sejahtera Posdaya, Pasir Mulya, West Bogor sub-district, Bogor district. The sample consists of 32 MFI members and 38 non-MFI members. The result shows that experiences in financial institutions and cosmopolitans significantly influence welfare. Factors influence the family welfare are family income, members’ perception to MFI, and members participation.